(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Charcoal is a renewable material, with a long history of use as the predecessor of fossil fuels, now beginning to regain its place in the market, as the global society is fighting the Climate change. Charcoal along with bio-oils, and pyrolysis gas or syngas is obtained through thermo-chemical conversion of biomass. There are several different turns the charcoal production development has taken. The oldest charcoal production technologies are the batch-type kilns, they are associated with lower costs, and are widely used in the world, mainly in developing countries. A more recent introduction in charcoal production is the continuous operation retort where the biomass is conveyed through different process stages, heating and drying, carbonization, and cooling. This technology draws up high capital investments, but can reach a high level of automation. Apart from these technologies charcoal can be also obtained as a by-product in liquid and gaseous fuel production via pyrolysis and gasification of biomass. Each of the production methods can yield variant quality charcoal with properties distinguishing different charcoal applications. The charcoal use varies from a high capacity fuel to a sustainable soil amendment, adsorbent, source of carbon in chemical reactions, and many more. In this study an evaluation of the charcoal quality parameters, depending on the applied technology, is carried out. The analysed data includes information retrieved from previous studies, as well as an experimental investigation of real life production facility.